Contribution to the Reduction of Annealing Processes in the Manufacturing of Valve Solenoids by Using Inline Measuring Technology in the Caulking Process - Freiherr von Lindenfels, Johannes; Heyder, Andreas; Funk, Stefan; Pigler, Stefan; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production IV, 2018)
Electromagnetic actors (solenoids) are used in automotive and automation technology as valve actors for pneumatics and hydraulics or as actuating and pressure solenoids. During assembly there are often press-in and caulking processes used. A central quality aspect of the final control elements is the adherence to defined actuating force ranges in order to ensure the switching process and at the same time to keep wear within limits. These defined force ranges can currently only be maintained by additional heat treatment of the parts. The hysteresis of the assembled unit can be influenced by the caulking. The objective of this paper is to propose the potential reduction of annealing processes by revealing the interdependencies between the magnetic interactions of the individual components and the assembly process parameters. In addition, errors in the caulking process are detected and prevented at an early stage. A magnetic characterization of the soft magnetic components and assemblies before and during their assembly is proposed. Furthermore, the integration of the measurement data into a process control system is intended. The precondition is the development and construction of measuring equipment and systems that can be used to assess the magnetic properties at an early stage of assembly. The assembly can then be adjusted in order to compensate batch fluctuations. As a consequence new materials can be used to eliminate complex annealing processes prior to assembly. <br
Keywords: Caulking; Hall Sensor; Inline Measuring Technology; Solenoids